PERELEK CULTURE: A SHARING EFFORT IN KUTA VILLAGE - Widiyanti, Sopi Aprilia; Wilodati, Wilodati (Jurnal Pendidikan Sosiologi dan Humaniora, 2023)
Perelek is one of the residents' efforts to show their existence by preserving this culture in social life in society. The method used is Literature Study; in collecting research data, the authors collect and analyze various sources through journals, books, and previous research, which are still related to the topic of discussion in this journal article. The results of this study indicate that the Kuta Indigenous Village Community still preserves the Beas Perelek by collecting one spoon of rice per day from each resident, who is collectively by the wife of the head of the local RT. This "perelek" also represents the generous side of every individual in that environment. On the other hand, this "perelek" shows the side of togetherness and solidarity among the people. The main goal with the existence of Perelek is to increase community participation in social responsibility and concern that needs to be included amid today's developments. Therefore, the existence and resilience of the perelek culture that still exists in the Kuta Traditional Village is a particular form of inter-community concern. The principles held by the local community have enabled this "perelek" culture to survive even amid the development of the globalization era.